2019
DOI: 10.3389/fcell.2019.00181
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Protein Sorting at the Trans-Golgi Network and Endosomes Through Super-Resolution Imaging

Abstract: The trans-Golgi network (TGN) and endosomes are essential protein sorting stations in the secretory transport pathway. Protein sorting is fundamentally a process of spatial segregation, but the spatial relationships among the proteins that constitute the sorting machinery have not been systematically analyzed at high resolution in mammalian cells. Here, using two-color STORM imaging, we show that the TGN/endosome-localized cargo adaptors, AP-1, GGA2 and epsinR, form elongated structures of over 250 nm in lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The percentage of colocalization was quantified by calculating the percentage of overlapped pixels using Fiji was used for calculating, based on a modified quantification method (Guo et al, 2008;Huang et al, 2019). The quantification is performed using the following procedures: (1) a threshold was chosen manually based on the original gray scale images;…”
Section: Quantification Of the Percentage Of Colocalizationmentioning
confidence: 99%
“…The percentage of colocalization was quantified by calculating the percentage of overlapped pixels using Fiji was used for calculating, based on a modified quantification method (Guo et al, 2008;Huang et al, 2019). The quantification is performed using the following procedures: (1) a threshold was chosen manually based on the original gray scale images;…”
Section: Quantification Of the Percentage Of Colocalizationmentioning
confidence: 99%
“…Interestingly, a recent study perfomed in Schizosacchoromyces pombe demonstrated that GGAs in collaboration with clathrin adaptors indeed contribute to efficient retrograde transport of Vps10, yeast's MPR homologue, from the prevaculaor endosome to the TGN (Yanguas et al, 2019). In addition, despite the functional relationship of GGA2 and AP-1 adaptors, it is suprising to observe that they are spatially segregated from each other to a considerable extent (Huang et al, 2019). Our results showing reduced CDMPR transport to the TGN using a sulfation-based approach strongly support a contribution to retrograde transport by GGAs.…”
Section: Discussionmentioning
confidence: 99%
“…Two‐colour stochastic optical reconstruction microscopy (STORM) has been very recently used to analyse cargo sorting at the plant TGN/EE (Huang et al ., 2019) through a high‐resolution visualization of TGN/EE and endosome‐localized cargo adaptors. In particular, the spatial distribution of clathrin heavy chain (CHC) and of one of the major cargo adaptors responsible for sorting at the TGN/EE, the γ subunit of adaptor complex 1 (γ1), was examined using the two colour STORM imaging followed by 3D super resolution imaging.…”
Section: Advanced Live‐cell Microscopy To Study the Tgn/eementioning
confidence: 99%
“…In particular, the spatial distribution of clathrin heavy chain (CHC) and of one of the major cargo adaptors responsible for sorting at the TGN/EE, the γ subunit of adaptor complex 1 (γ1), was examined using the two colour STORM imaging followed by 3D super resolution imaging. This approach allowed observing and resolving elongated structures of 250 nm in length associated with the cargo adaptor protein (AP1) at the TGN/EE (Huang et al ., 2019). The high resolution of the images produced with this approach allowed not only a precise quantification to establish a percentage of association between the CHC and AP1 but also provided direct evidence supporting the sorting of specific cargo adaptors in distinct microdomains of the TGN/EE and demonstrating differential sorting processes.…”
Section: Advanced Live‐cell Microscopy To Study the Tgn/eementioning
confidence: 99%